Percebendo a affordance alcançável: efeito da demanda postural - Bruna Silva Avelar (2013)
The present dissertation was designed to promote a better understanding of perceptual capabilities supporting reaching performance. In particular, three experiments were performed to determine whether young, healthy individuals are sensitive to modifications in their reaching performances induced by manipulation of the postural demands involved in executing a maximal reach. The results demonstrated that factors known to affect postural demands (mass of assistive devices used in reaching and stability of support surface) consistently affect maximum reaching capability. The greater the magnitude of the mass and the instability of the surface, the shorter the reachable distance is. However, sensitivity to the effect of these factors on reaching capabilities, prior to execution of reach, seems to be context dependent. When variations in reaching capabilities induced by changes in postural demands are not detected, overestimation of the perceived maximal reachable distance is observed. Thus, sensitivity to the postural demands present in the context of activity seems fundamental for successful perception of the limit that separates regions in space where targets are reachable from regions where targets are not reachable. The aspects of context that favor sensitization to the effects of postural demands on reaching performance, and consequently, that support precise perception of maximal reachable distance are yet to be uncovered. However, the recent history of exposure to high postural demands seems relevant to promote such sensitization.